Predictors of Colorectal Cancer Screening in Two Underserved U.S. Populations: A Parallel Analysis - Bernardo, Brittany M.; Gross, Amy L.; Young, Gregory; Baltic, Ryan; Reisinger, Sarah; Blot, William J.; Paskett, Electra Diane (Frontiers in Oncology, 2018)
BACKGROUND: Despite declining colorectal cancer (CRC) incidence and mortality rates in the United States, significant geographic and racial disparities in CRC death rates remain. Differences in guideline-concordant CRC screening rates may explain some of these disparities. We aim to assess individual and neighborhood-level predictors of guideline-concordant CRC screening within two cohorts of individuals located within CRC mortality geographic hotspot regions in the U.S. METHODS: A total of 36,901 participants from the Southern Community Cohort Study (SCCS) and 4,491 participants from the Ohio Appalachia CRC screening study were included in this study. Self-reported date of last CRC screening was used to determine if the participant was within guidelines for screening. Logistic regression models were utilized to determine the association of individual-level predictors, neighborhood deprivation and residence in hotspot regions on the odds of being within guidelines for CRC screening. RESULTS: Lower household income, lack of health insurance and being a smoker were each associated with lower odds of being within guidelines for CRC screening in both cohorts. Area-level associations were less evident, although up to 15% lower guideline adherence was associated with residence in neighborhoods of greater deprivation and in the Lower Mississippi Delta, one of the identified CRC mortality hotspots. CONCLUSIONS: These results reveal the adverse effects of lower area-level and individual socioeconomic status on adherence to CRC guideline screening.